2002
DOI: 10.1046/j.1365-2923.2002.01229.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress in doctors and dentists who teach

Abstract: Working as a doctor or dentist may entail higher levels of stress than are experienced by the general population. In some situations adding in the role of teacher reduces this stress, but more research is needed to explain this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
1
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 36 publications
2
60
1
6
Order By: Relevance
“…Rutter, Herzberg and Paice found that dentists who take on teaching or leadership roles with other professionals, in addition to clinical duties, found that it may reduce stress. 22 This study suggested that the reason for this reduction is it lessened isolation and increased self-esteem in response to the attention from dental students. However, not all stressful situations can be eliminated from dentistry.…”
Section: Quality Of Life Following Retirementmentioning
confidence: 84%
“…Rutter, Herzberg and Paice found that dentists who take on teaching or leadership roles with other professionals, in addition to clinical duties, found that it may reduce stress. 22 This study suggested that the reason for this reduction is it lessened isolation and increased self-esteem in response to the attention from dental students. However, not all stressful situations can be eliminated from dentistry.…”
Section: Quality Of Life Following Retirementmentioning
confidence: 84%
“…2 However, as mentioned previously, 1 year of experience still may not be ideal for quality clinical instruction due to time constraints placed on GAATs. 20 To this end, veteran nursing and medical educators 21,22 recommended that clinical teaching be reserved for those clinicians who have had several years of clinical experience. In this way, the clinician could mature in the role of health care provider before also assuming the role of clinical teacher.…”
Section: Degree Of Role Strainmentioning
confidence: 99%
“…In this way, the clinician could mature in the role of health care provider before also assuming the role of clinical teacher. [21][22][23] The NCAA division classification of the institution also affected the degree of role strain experienced by ACIs. The ACIs at Division II schools reported a higher degree of inter-role conflict (eg, dual appointments in athletics and academics), suggesting that the expectations associated with these 2 roles are in conflict.…”
Section: Degree Of Role Strainmentioning
confidence: 99%
“…This syndrome particularly affects occupational groups characterized by highly emotional relationships and a high professionalism of services provided (Rutter, Herzberg & Paice, 2002). Undoubtedly then, the occupational group of doctors meets the two essential criteria in the relation with the patient, i.e.…”
Section: Introductionmentioning
confidence: 99%